Analysis of Autonomous Wheelchair Navigation Technologies in the Past Five Years: A Systematic Review - Bakouri, Mohsen; Alqarni, Abdullah; Alanazi, Sultan; Alassaf, Ahmad; AlMohimeed, Ibrahim; Alqahtani, Tareq (International Journal of Online and Biomedical Engineering (iJOE), 2025)
This study aims to analyze the latest developments in wheelchair navigation assistance systems. This analysis is obtained by conducting a systematic review of the significance of technologies for performance metrics and control strategies used. The autonomous category, input methods, tools used, technology used, test type, and accuracy were selected as reference metrics that set the comparison criteria, highlight innovative approaches, and discuss the development field of wheelchairs. In this work, to conduct the systematic review, four databases were identified. These include Science Direct, Taylor and Francis Online, Springer Journals, and IEEE Xplore. The pool of keywords set was selected to identify research articles published in the past five years. Inclusion and exclusion criteria were set to select the relevant studies that were consistent with the objectives of this study. Based on these criteria, 46 research papers were selected that met the inclusion requirements. The review study showed that wheelchair technology models such as autonomous control, 3D localization, and brain-computer interfaces (BCIs) were more precise in navigation and increased user independence. This systematic planning will help researchers, engineers, and practitioners make more realistic decisions to fill the gaps in available navigation aids and propose new and improved solutions for innovative assistant applications to ensure safety and accurate navigation. This study has many implications, especially the impact of reducing deaths and serious injuries among people with disabilities who use advanced technology wheelchairs.